THE STRATEGIC BENEFITS AND CHALLENGES IN THE USE OF CUSTOMER RELATIONSHIP MANAGEMENT SYSTEMS AMONG COMMERCIAL BANKS IN KENYA - Muro, Maximillah Bitutu; Magutu, Peterson Obara; Getembe, Kepha Nyankora (European Scientific Journal, ESJ, 2013)
Nowadays, many businesses such as banks, insurance companies, and other service providers have realized the importance of Customer Relationship Management (CRM) and its potential to help them acquire new customers, retain existing ones and maximize their lifetime value. At this point, close relationship with customers requires strong coordination between IT and marketing departments to provide a long-term retention of their customers. The purpose of this study was to establish the use of CRM systems and further determine the challenges facing the use of CRM systems among the commercial banks in Kenya. The study used descriptive design. The study targeted forty five (45) commercial banks in Kenya. Primary data was obtained using self administered questionnaires. The successfully filled up questionnaires containing responses were first edited for accuracy, consistency and completeness. The data from questionnaires was analyzed using procedures within statistical package for social sciences (SPSS). The responses were analyzed using measures of dispersion (mean and standard deviation), distribution tables, quartiles (percentiles) and graphical analysis so as to explain the response rates from various respondents. The study found out that IT ensured personalized attention to the customers and also facilitated variety of products offered by the bank. It enabled the bank to understand and serve customers better than their competitors, developed and improved new products for the customers. It also improved processes and relationships with its customers and business partners and further built a long lasting relationship with the customers, increased revenues and profits. The study concludes that CRM is a useful business strategy and most essential to banks which have a day to day dealing with the customers. It is beneficial for all stakeholders: customers, employees, and investors. Good maintenance of CRM system can enhance increased performance through revenues and profits since adoption of CRM builds a long lasting relationship. The study recommends that banks should recognize the strategic role played by CRM as well as the increased importance ascribed to CRM in the future. They should recognize the diversity of experience and needs of different customers. Moreover, banks should hire professional people to deal with the system efficiently especially when the system is complex.